Genocide Denial: A Form of Evil or a Type of Epistemic Injustice? (European Journal of Interdisciplinary Studies, 2018)
In this paper, I bring together the philosophical scholarship on evil and the literature on “epistemic injustice” in order to assess effective vocabulary to understand the phenomenon of genocide denial. I use the term “denial” to denote the discursive political tactic that makes the evil of genocide invisible. Adi Ophir’s discussion of “two orders of evil” allows us to consider genocide denial as a form of evil. For what Ophir identifies as a second-order evil, another stream of scholarship suggests the term “epistemic injustice.” This latter literature can also be deployed effectively in treating the question of genocide denial, insofar as it provides an interdisciplinary approach rather than a strictly philosophical one. Epistemic injustice scholars focus on different types of unfair treatment in the realm of knowledge-production, and they agree that exclusion, silencing, invisibility and distorted representation are major forms of epistemic injustice. I argue that both scholarships are crucial to draw out conceptual frameworks for understanding the specific case of genocide denial. Furthermore, I think that interdisciplinary approaches informed by the social sciences are essential to map out the real life implications of the injustices that are implemented through denial.